The impact of incomplete clinical information and initial biopsy technique on the histopathological diagnosis of cutaneous melanoma. (23rd August 2021) - Kok, Yonatan; Scott, Karen; Pham, Alan; Liu, Wenyuan; Roberts, Hugh; Pan, Yan; McLean, Catriona; Chamberlain, Alex; Kelly, John W.; Mar, Victoria J.
Abstract: Background/Objectives: Increased rates of histopathological misdiagnosis of melanoma have been associated with incisional punch more so than shave biopsy when compared with complete excisional biopsy. It is unknown how the increasing utilisation of shave biopsy may impact melanoma diagnosis. The extent to which the provision of clinical information to the pathologist may improve diagnostic accuracy remains unclear. This study assessed the impact of both initial biopsy technique and provision of adequate clinical information to pathologists on the accuracy of histopathological diagnosis of melanoma and disease progression. Methods: We conducted a retrospective cohort with nested case‐control study of all histopathological false‐negative and false‐positive melanoma diagnoses from January 2014 to May 2019 from the Victorian Melanoma Service electronic database. Cases were assessed for the initial biopsy type, provision of clinical information on pathology request forms and disease progression associated with false‐negative diagnosis. Results: Partial shave biopsy had higher odds of false‐negative (OR 5.19, 95% CI 2.89–9.32; P  < 0.001) and false‐positive diagnoses (OR 1.95, 95% CI 1.45–2.63; P  < 0.001) of melanoma when compared with elliptical excisional biopsy. These odds ratios were comparable with those found with incisional punch biopsy. Providing the suspected clinical diagnosis to pathologists also reduced the odds of false‐negative diagnosis with melanoma progression by 3.8‐fold ( P  = 0.02). Conclusion: The choice of initial biopsy technique and providing the suspected clinical diagnosis to pathologists are important for correct histopathological diagnosis of cutaneous melanoma and prevention of further disease progression.